2017
DOI: 10.3892/mmr.2017.7467
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of berberine and Coptischinensis extract on T2MD rats and associated islet Rin-5f cells

Abstract: The aim of the present study was to compare the different effects of berberine (Ber) and Coptischinensis extract (CCE) on a rat model of type 2 diabetes mellitus (T2DM), and the islet Rin‑5f cell line was used to examine the differences between Ber and CCE and the underlying mechanisms. CCE was extracted and purified prior to analysis. Male Sprague‑Dawley rats were provided with a high‑fat diet to induce insulin resistance prior to injecting with streptozotocinto establish the T2DM model, the T2DM rats were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…T2DM is characterized by hyperglycemia, associated with insulin resistance and insufficient insulin secretion due to pancreatic β-cell dysfunction. Our literature survey revealed that berberine protects pancreatic cells and restores insulin secretion by β-cells [56,[137][138][139][140][141][142]. Brain insulin resistance is a key feature of AD and related dementias, and evidence suggesting the link between systemic and brain insulin resistance is growing [164,165].…”
Section: Protection Of Pancreasmentioning
confidence: 92%
See 1 more Smart Citation
“…T2DM is characterized by hyperglycemia, associated with insulin resistance and insufficient insulin secretion due to pancreatic β-cell dysfunction. Our literature survey revealed that berberine protects pancreatic cells and restores insulin secretion by β-cells [56,[137][138][139][140][141][142]. Brain insulin resistance is a key feature of AD and related dementias, and evidence suggesting the link between systemic and brain insulin resistance is growing [164,165].…”
Section: Protection Of Pancreasmentioning
confidence: 92%
“…Both clinical and preclinical studies ( Table 3) have shown that berberine could alleviate insulin resistance and reduce blood glucose [60,72,75,124,139,140], which is likely due to the protection of pancreatic β-cells [56,137,140] and restoration of insulin secretion [56,139,142]. Molecular mechanisms underlying berberine's pancreatic protection include modulation of anti-apoptotic Bax and pro-apoptotic Bcl-2 expression levels [138], activation of AMPK [139,142], restoration of sirtuin 1 (SIRT1) [141] and induction of uncoupling protein 2 (UCP2) [142].…”
Section: Prevention Of Mets 321 Pancreatic Dysfunctionmentioning
confidence: 99%
“…Berberine and CRE exerted similar protective effect on islet β cells by improving islet β cell proliferation and the protein level of PARP1 (Jiang et al. 2017). Inflammation and oxidation are closely associated with DM.…”
Section: Pharmacologymentioning
confidence: 99%
“…Berberine organic acids (BOAs) were found to be comparable to berberine hydrochloride (BH) in terms of hypoglycaemic effects, they were but superior with regard to safety from hyperchloraemia in T2DM rats (Li et al, 2017). Coptis chinensis (containing berberine) and BBR exerted similar effects when used for the treatment of T2MD rats, mainly via the stimulation of the pancreatic secretion of insulin (Jiang et al, 2017). Berberine chloride was a stronger antidiabetic agent than BBR or canagliflozin alone with fewer side effects on kidneys in the diabetic mice (Cai-Ming et al, 2016).…”
Section: In Vivo Activities Against Diabetes and Metabolic Diseasesmentioning
confidence: 99%